HUBUNGAN ANEMIA DALAM KEHAMILAN IBU DENGAN KEJADIAN BAYI BERAT LAHIR RENDAH - Niar, Niar; Hasriani, Hasriani (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2024)
Anemia is a common medical problem in pregnancy. So far, whether maternal anemia affects the health of mother and baby is still uncertain. Maternal anemia is generally considered a risk factor for low birth weight (LBW) babies. The aim of this study was to determine the relationship between anemia in maternal pregnancy and the incidence of LBW babies at Hajja Andi Depu Regional Hospital. This research is a quantitative analysis research with a cross sectional design. The research was carried out by taking medical record data from pregnant women who gave birth to low birth weight babies at Hajja Andi Depu Hospital, Polewali Mandar Regency. The sampling method is consecutive sampling of 20 samples. Bivariate analysis used using chi-square obtained a significant value, namely ???? 0.000 < 0.05. There is a relationship between maternal pregnancy and the incidence of LBW at Hajja Andi Depu Regional Hospital.